Labor Supply as a Choice among Latent Job Opportunities. A Practical Empirical Approach - John K. Dagsvik; Zhiyang Jia (Statistics Norway, Research Department, 2006)
In this paper, we discuss aspects of a particular framework for modeling labor supply and the application of this approach in practical policy simulation experiments. This modeling framework differs from the standard models of labor supply in that the notion of job choice is fundamental. Specifically, the worker is assumed to have preferences over a latent worker-specific choice set of jobs from which he or she chooses his or her preferred job. A job is characterized with fixed (job-specific) working hours and other non-pecuniary attributes. As a result, observed hours of work are interpreted as the job-specific (fixed) hours of work that is associated with the chosen job. We then show that our framework is practical with respect to applications in empirical analysis and simulation experiments, and is able to produce satisfactory out-of-sample predictions by estimating the model on Norwegian microdata from 1997 and predicting the corresponding microdata from 2003.
Keywords: J22; C51; 330; Labor supply; non-pecuniary job attributes; non-convex budget sets; latent choice sets; random utility models.